A sociocultural-historical view of "knowledge": management understandings and applications. (1st January 2000) - Small, Michael W.; Dickie, Laurence
"Knowledge" and "knowledge management" are two new areas of interest to those who have an interest both in management theory and management practice. The article refers to "knowledge management" (KM), "organisational learning" (OL), and a "learning organisation" (LO) as concepts which have relevance for today's CEO's and others in management. Reference is made to a recent discussion paper on higher education research and research training and the importance of generating new knowledge in contemporary society. "Knowledge" is then discussed in its literary-historical context with examples from classic times, through the centuries to the present day. The paper concludes with an analysis how "knowledge" and "new knowledge" are managed in industry, and the implications which these have for contemporary management practice.